The mechanism of Bacillus subtilis regulating the underground system and bamboo shoot quality of Lei bamboo (Phyllostachys praecox) under bamboo charcoal addition - Huang, KaiWen; Peng, YuWen; Wang, ZhenMing; Luo, HongYang; Wen, ZuoRong; Bi, YuFang; Wang, AnKe; Qin, JiaXing; Du, XuHua (Frontiers in Plant Science, 2025)
IntroductionLei bamboo (Phyllostachys praecox) is widely cultivated due to its early-season bamboo shoots, but the mechanisms linking its underground system regulation and shoot quality remain unclear. MethodsThis study assessed the impact of Bacillus subtilis (T1, 250 kg·hm-2), bamboo charcoal (T2, 1500 kg·hm-2), and their combination (T3) on soil chemistry, whips and roots morphology and biomass, hormone regulation, and the biochemical quality of bamboo shoots. ResultsTreatment T1 notably increased soil total organic carbon and nitrogen, promoted whip development and root activity. These improvements were linked to elevated levels of GA, IAA, and CTK hormones and reduced ABA levels, which led to higher starch, soluble sugar, protein, and total amino acid contents in the bamboo shoots. Treatment T2 increased biomass of whips and roots, but also raised ABA and organic acids, improved protein and amino acids, while decreasing starch and sugar accumulation. The combined treatment T3 showed antagonistic effects, lowering amino acid content. The comprehensive evaluation ranking of bamboo shoot quality was T1 > T2 > T3 > CK. DiscussionThese results reveal a new “soil chemistry-hormone-morphology and biomass-quality” cascade mechanism, and emphasize Bacillus subtilis and bamboo charcoal as promising fertilizers for producing sweet, crisp, and flavorful bamboo shoots. For practical application, it is advised that farmers apply 250 kg·hm-2 Bacillus subtilis as the fertilizer choice for the production of sweet, crisp and juicy bamboo shoots, and 1500 kg·hm-2 bamboo charcoal as the fertilizer choice for the production of bamboo shoots with unique flavors before mulching each November to enhance bamboo shoot quality and supply high-value raw materials for the bamboo industry.